Early Development of the Gut Microbiome and Immune-Mediated Childhood Disorders - Li, Min; Wang, Mei; Donovan, Sharon M. (Seminars in Reproductive Medicine, 2014)
The human gastrointestinal tract inhabits a complex microbial ecosystem that plays a vital role in host health through its contributions to nutrient synthesis and digestion, protection from pathogens, and promoting maturation of host innate and adapt immune systems. The development of gut microbiota primarily occurs during infancy and is influenced by multiple factors, including prenatal exposure; gestational age; mode of delivery; feeding type; pre-, pro-, and antibiotic use; and host genetics. In genetically susceptible individuals, changes in the gut microbiota induced by environmental factors may contribute to the development of immune-related disorders in childhood, including atopic diseases, inflammatory bowel disease, irritable bowel syndrome, and necrotizing enterocolitis. Pre- and probiotics may be useful in the prevention and treatment of some immune-related diseases by modulating gut microbiota and regulating host mucosal immune function. The review will discuss recent findings on the environmental factors that influence development of gut microbiota during infancy and its potential impact on some immune-related diseases in childhood. The use of pre- and probiotics for prevention and intervention of several important diseases in early life will also be reviewed.
Keywords: microbiota; gastrointestinal; allergy; asthma; immune